The paleo-oceanic environment and organic matter enrichment mechanism of the early Cambrian in the southern Lower Yangtze platform, China - Zhou, Dongsheng; Dong, Hezheng; Huang, Xiaowei; Liang, Yufei; Deng, Ziyan; Huang, Lei; Jiang, Shu (Marine and petroleum geology, 2024)
This study focuses on the Lower Yangtze Platform located in southern Anhui Province, focusing on the black shale of the early Cambrian Hetang Formation as the primary research subject. Three field sections representing distinct sedimentary structural units were selected for investigation. Analytical methodologies encompassing organic geochemistry, elemental geochemistry, and scanning electron microscopy were employed to reconstruct paleo-oceanic environmental conditions. These analyses aimed to elucidate the characteristics of marine surface productivity and identify the factors controlling organic matter formation, thereby establishing a model for organic matter accumulation processes. These findings suggest that the Jiangnan paleo-uplift exerted differentiated control over organic matter formation and accumulation. Specifically, the barrier function of the paleo-uplift fostered a relatively enclosed and restricted water environment in certain regions, which proved conducive to the formation, accumulation, and preservation of organic matter. Furthermore, the paleo-upwelling system and hydrothermal groundwater circulation triggered by the activation of the Jiangnan deep fault played crucial roles in controlling the formation and accumulation of organic matter in the early Cambrian. Notably, the research also revealed that intermittent hydrothermal activity had a dual impact on organic matter accumulation within various paleo-oceanic settings. This process potentially facilitated organic matter enrichment and led to the dilution of organic matter concentrations. [Display omitted] •Reveals the significant impact of early Cambrian marine conditions on organic matter deposition.•Identifies hydrothermal sources and evaluates their differential impact on organic matter accumulation.•Analyzes key sedimentary and geochemical factors controlling organic matter enrichment.•Proposes a new model for early Cambrian organic matter accumulation, offering a framework for related studies.